Sentinel lymph node mapping with Indocyanine green fluorescence (ICG) for pediatric and adolescent tumors: a prospective observational study - Luca Pio; Celine Richard; Tarek Zaghloul; Andrew J. Murphy; Andrew M. Davidoff; Abdelhafeez H. Abdelhafeez (Scientific Reports)
Abstract Sentinel lymph node biopsy (SLNB) is an important technique in the staging of pediatric melanomas, sarcomas, and potentially useful for other solid tumors. Precise visual localization of the sentinel lymph node (SLN) during the operation is a key challenge of this procedure. Presently, the gold standard method employing Technetium 99 (99mTc) for localization carries a notable false-negative rate. In this context, we propose evaluating the use of Indocyanine Green near-infrared (ICG-NIR) as a supplementary tool to enhance the identification of SLN. A prospective observational study focused on pediatric and adolescent patients undergoing SLNB using ICG-NIR at a single institution from 2019 to 2022. Lymphoscintigraphy with 99mTc was performed before surgery and 99mTc was detected intraoperatively using a handheld gamma probe. ICG was administered intraoperatively and assessed using transcutaneous NIR. The study collected demographic data, intra-operative findings (Technetium 99 m, ICG fluorescence), and histopathological data. Eight patients with a median age of 16 years (range: 8–19 years) underwent fluorescence-guided sentinel lymph node harvesting with 100% sensitivity. Sentinel lymph node fluorescence was verified with a positive radiosignal in all patients. No adverse events were recorded. Fluorescence-guided assessment of the lymphatic system is both feasible and effective for sentinel lymph node identification. Nevertheless, larger-scale studies are essential to establish indocyanine green as a viable alternative rather than a complementary technique alongside the gold-standard radioisotope-guided method for sentinel lymph node assessment in children.